Clinical outcomes of multifetal pregnancy reduction in trichorionic and dichorionic triplet pregnancies: A retrospective observational study - Yaqiong Liu; Yan Shen; Hong Zhang; Yi Tang; Guangxiu Lu; Ge Lin; Fei Gong (Elsevier, 2019)
Objective: To observe the pregnancy and perinatal outcomes of trichorionic triplet (TCT) and dichorionic triplet (DCT) pregnancies with or without multifetal pregnancy reduction (MFPR). Materials and methods: This was a retrospective study of 732 TCT and 118 DCT pregnancies after IVF/ICSI cycles between October 1999 and May 2014 at the Reproductive & Genetic Hospital of CITIC-Xiangya. The TCT and DCT groups were subdivided into three subgroups: MFPR to single fetus group, MFPR to twins group and expectant group. Pregnancy and perinatal outcomes were compared between different subgroups. Results: The resulting subgroups were TCT-Expectant (n = 40), TCT to twin (n = 610), TCT to single (n = 22), DCT-Expectant (n = 17), DCT to twin (n = 50), and DCT to single (n = 22). The groups with MFPR had the better pregnancy and perinatal outcomes. Meanwhile, the significantly higher abortion rates but lower live birth and take home baby rates were found in TCT-Expectant group and DCT-Expectant group (all P < 0.05). Besides, the abortion rate of DCT-Expectant group was much higher than TCT-Expectant group (41% verse 15%, P = 0.032). As for the perinatal outcomes, retaining single fetus group showed the advantage of higher birth weight, and elder gestational age in both DCT and TCT pregnancies (all P < 0.05). Conclusion: For DCT and TCT pregnancies, MFPR application could reduce the miscarriage rate, while improving live birth and take home baby rates compared to the expectant groups. Especially, when reduced to a single fetus, MFPR could provide the better perinatal outcomes. Keywords: Trichorionic triplet pregnancies, Dichorionic triplet pregnancies, MFPR, Pregnancy outcomes, Perinatal outcomes